Transcriptome and metabolome profiling unveil the mechanisms of Ziziphus jujuba Mill. peel coloration. (15th May 2020) - Zhang, Qiong; Wang, Lili; Liu, Zhiguo; Zhao, Zhihui; Zhao, Jin; Wang, Zhongtang; Zhou, Guangfang; Liu, Ping; Liu, Mengjun
Highlights: Transcriptomic and metabolic analysis of jujube fruit peel coloring during ripening. Strong accumulation of malvidin and delphidin correlated with peel reddening. Differentially expressed genes in the flavonoid synthesis pathway identified. 3 UFGT genes may play essential functions for the accumulation of anthocyanins. Abstract: Coloring is an important external quality of jujube fruit ( Ziziphus jujuba Mill.), however during long-term storage, its commercial value degrades as the peel color and lustre significantly fade. Here, the gene expression and metabolite concentration were profiled in the fruit peel of jujube harvested at three ripening periods to elucidate the color formation mechanism. A strong accumulation of malvidin 3-O-glucoside and delphinidin 3-O-glucoside correlated with the reddening of jujube peel. At the onset of the fruit ripening, strong activities of the genes in the early steps of the flavonoid biosynthetic pathway were observed. During the last ripening periods, three UDP-glucose flavonoid 3-O-glucosyltransferase ( UFGT ) involved in the accumulation of anthocyanins were significantly increased and their proper manipulation could delay the peel reddening. This study sheds light on the metabolic pathways and candidate genes underlying the peel coloration in jujube and lays a foundation for the improvement of jujube fruit appeal during long-term storage.